1993
DOI: 10.1007/bf00146260
|View full text |Cite
|
Sign up to set email alerts
|

A longitudinal study on the incidence and transmission patterns of HIV, HBV and HCV infection among drug users in Amsterdam

Abstract: In the present study data on the incidence of HBV and HCV were used to indicate the prevalence of and trends in risk behavior, assuming that drug users (DUs) who become infected with HBV or HCV are also at risk for infection with HIV. In addition, we determined to that extent the transmission patterns of HIV, HBV and HCV differed. DUs were selected from a cohort study in Amsterdam, had at least one follow-up visit between December 1985 and September 1989 and reported never to have had homosexual contacts. Amon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
62
4
2

Year Published

1995
1995
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 143 publications
(77 citation statements)
references
References 33 publications
9
62
4
2
Order By: Relevance
“…4,8,10,11 At the 2 sites in our study, the HCV infection prevalence was lower than was reported in these studies, and we found a longer time of injecting (>6 years) before reaching a peak prevalence of infection. Additionally, our reported prevalence was lower than the prevalence reported in young injection drug users in Baltimore.…”
Section: Discussioncontrasting
confidence: 72%
See 1 more Smart Citation
“…4,8,10,11 At the 2 sites in our study, the HCV infection prevalence was lower than was reported in these studies, and we found a longer time of injecting (>6 years) before reaching a peak prevalence of infection. Additionally, our reported prevalence was lower than the prevalence reported in young injection drug users in Baltimore.…”
Section: Discussioncontrasting
confidence: 72%
“…4,[7][8][9] However, we did not find direct syringe sharing, which is an established risk factor for HCV infection among injection drug users, [8][9][10][11] to be associated with prevalent HCV infection. Nevertheless, several correlates of HCV infection in our sample may have served as markers for syringe sharing.…”
Section: Discussionmentioning
confidence: 90%
“…5% in Limburg. Other studies targeting populations of non-IDU have reported prevalence rates widely varying between 2 and 25 % [4,[11][12][13][14][15][16][17][18][19][20][21].…”
Section: Discussionmentioning
confidence: 99%
“…HCV incidence rates in IDUs vary between 10% and 30% per year and are generally 4 to 100 times higher than the incidence of HIV in the same population. [3][4][5][6] HBV incidence in IDUs is somewhat lower, at 5%-10% per year. [2][3][4][5][6] Information about the epidemiology of hepatitis B and C in IDUs is also obtained from data on acute hepatitis cases reported to public health disease surveillance systems.…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5][6] HBV incidence in IDUs is somewhat lower, at 5%-10% per year. [2][3][4][5][6] Information about the epidemiology of hepatitis B and C in IDUs is also obtained from data on acute hepatitis cases reported to public health disease surveillance systems. In the sentinel hepatitis surveillance studies sponsored by the Centers for Disease Control and Prevention (CDC), 43% of acute hepatitis C in 1992-1995 and 13% of hepatitis B in 1990-1992 was associated with drug injection.…”
Section: Introductionmentioning
confidence: 99%